Effects of Environmental Problems on Human Healthy in Iraq: A Review - Aqeel M. Ali Al-Lami (Journal of Global Pharma Technology, 2016)
Pollution consider the most dangerous that faced by human and living organisms on the earth, oxygen and water is the necessary sources for our life, air and water pollution effects on human, animals and plants .Ecology study the relations between living things and its habitat forming certain ecosystem. Ecosystems explain any relation types between living organism and the environment. There are many problems in earth affected continue of life, ozone depletion permit to entry of U.V. rays from sun to earth, and cause increase dangerous for human, animals, microorganisms, and plants. Desertification and deforestation in lands acts for decreasing of vegetation area. Biological diversity must be stay with no effects, also decreasing in fresh water determine life stability.Keywords: Pollution, Ozone, Health, Cancer.